(untitled) (Bangladesh Journal of Medical Science, 2009)
Background: The metabolism of several trace elements has been reported to alter in diabetes mellitus and these elements might have specific roles in the pathogenesis and progress of this disease. Objective: The aim of the present study was to investigate serum levels of copper, zinc, chromium, magnesium and manganese in type 2 diabetic patients and their possible association with age, glycemic status and duration of diabetes. Methodology: The comparative study included 116 type 2 diabetic patients and 40 non-diabetic subjects. Fasting plasma glucose and HbA1c were determined by the glucose oxidase method and affinity chromatography respectively. The element concentrations were measured by means of an atomic absorption spectrophotometer after microwave-induced acid digestion. Results: Mean (±SD) Mg and Zn levels were significantly reduced in blood samples of diabetic patients as compared to control subjects (p<0.0001-<0.05). The alterations observed in serum levels of copper and manganese was not significant among diabetic and normal subjects. Glycemic status, duration of diabetes and age did not effect the trace elements concentrations. Conclusion: The results confirm that deficiency and efficiency of some essential trace metals may play a role in the development of diabetes mellitus. Key words: Trace elements, glycemic status, type 2 diabetes. DOI: 10.3329/bjms.v8i3.3983 Bangladesh Journal of Medical Sciences Vol.8(3) 2009 p52-56